Mating plans for breeding trials using generalized row-column designs - DATTA, ANINDITA; JAGGI, SEEMA; VARGHESE, CINI; VARGHESE, ELDHO; HARUN, MOHD; BHOWMIK, ARPAN (The Indian Journal of Agricultural Sciences, 2021)
Generalized Row-Column (GRC) designs are used where there is more than one unit in each row-column intersection. Mating plan is a systematic procedure of producing the progenies. Diallel and triallel crosses are some examples of mating plans. In literature there are many mating plans which are developed using block/row-column designs. The objective of the present study is to obtain mating plans using GRC designs. The research work has been done at ICAR-IASRI during 2019-20. Here, methods of obtaining partial diallel crosses (PDC) and partial triallel crosses (PTC) plans using different classes of GRC designs have been described. The plans obtained using these designs will yield smaller degree of fractionation thereby reducing resources.